Designing a helpdesk ticketing system to improve the efficiency of IT support services on an XYZ company-based web-site using the Laravel framework - Mohamad Nur Wahyuddin; Dhanny Permatasari Putri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
PT XYZ company requires a Helpdesk Ticketing system that can enhance the efficiency of their IT support services. Hence, this study aims to design and implement a web-based Helpdesk Ticketing System using the Laravel framework. The system is designed to assist the IT department in efficiently responding to and addressing employee issues. The research methodology includes user requirement analysis, system design, and application development using the Laravel framework. During the requirement analysis phase, the author identifies user needs and determines the essential features that should be present in the system. Subsequently, the system is designed, considering efficient architecture and design principles. In the development stage, the author utilizes the Laravel framework to build the Helpdesk Ticketing System. The selection of this framework is based on its capability to expedite the development process and provide the required features for the system. Additionally, the author conducts testing using the Black Box Testing method to ensure the system's functionality. The outcome of this research is a web-based Helpdesk Ticketing System that efficiently assists the IT department in handling employee issues. The system allows employees to report problems through the website, and the IT team can easily respond to and manage incoming tickets. With the implementation of this system, it is expected that the efficiency of IT support services will increase at PT XYZ.